2015
DOI: 10.1016/j.breast.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

How to compare the oncological safety of oncoplastic breast conservation surgery – To wide local excision or mastectomy?

Abstract: Striking similarities found between OBCS and mastectomy patients' histopathological results are in sharp contrast with previously published data. This study suggests that oncological outcomes following OBCS should be compared to mastectomy besides WLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…This study showed that, compared to WLE, OBCS was applied to patients with more advanced malignant disease, which is consistent with our previously published results [2]. More ultrasound scans and biopsies were necessary after OBCS than after simple WLE.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This study showed that, compared to WLE, OBCS was applied to patients with more advanced malignant disease, which is consistent with our previously published results [2]. More ultrasound scans and biopsies were necessary after OBCS than after simple WLE.…”
Section: Discussionsupporting
confidence: 81%
“…The decision on indication and technique of OBCS was taken by either an oncoplastic breast surgeon alone, or a breast and a plastic surgeon together [2,12]. Patients at risk for developing significant postoperative breast deformity with standard WLE techniques were considered for OBCS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, unresolved controversies remain for oncoplastic breast conservation, including identification of a positive resection margin following glandular mobilization, accurate targeting of the tumour bed for a radiotherapy boost, the upper size limit for safe breast conservation, and sequencing of radiotherapy with two‐stage flap‐based partial breast reconstruction.…”
mentioning
confidence: 99%